Prevention Strategies for Cyberbullying Based on Hadiths: A Thematic Analysis of Hadiths Pertaining to Ethical Communication - Sartika, Dewi; Novendri S, Mochammad; Putri, Sajida; Mulyani, Resy (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This article seeks to investigate hadith-based strategies for the prevention of cyberbullying through a thematic analysis of the Prophet Muhammad’s teachings on communication ethics. The increasing prevalence of digital bullying highlights a widening disparity between technological advancements and the moral literacy of society, particularly in the context of social media usage. Employing a qualitative methodology grounded in library research, this study utilizes thematic hadith analysis (mawḍū‘ī) alongside sanad and matn criticism to verify the authenticity of the narrations. Additionally, it examines Indonesia’s cyber law framework, including the Electronic Information and Transactions Law (UU ITE). The findings reveal that moral principles such as adab al-ḥiwār (ethics of dialogue), emotional regulation, tazkiyat al-nafs (self-purification), and the reinforcement of ukhuwah (social solidarity) can be operationalized into practical preventive strategies applicable within educational institutions, family environments, and digital communities. Moreover, the integration of hadith values with contemporary regulatory frameworks, such as the UU ITE, facilitates a more holistic approach to combating cyberbullying, incorporating educational and reconciliatory mechanisms aligned with the concept of islāḥ (reconciliation). This study underscores that cyberbullying constitutes not only a technological challenge but also an ethical and spiritual concern necessitating a synergistic approach involving character development, digital literacy, and legal policy. The findings aim to contribute to the discourse on Islamic digital ethics and inform the development of hadith-based digital literacy modules.Abstrak: Artikel ini bertujuan mengkaji strategi pencegahan perundungan siber berbasis hadis melalui analisis tematik terhadap ajaran Nabi Muhammad terkait etika komunikasi. Fenomena meningkatnya perundungan digital menunjukkan adanya kesenjangan antara perkembangan teknologi dan literasi moral masyarakat, khususnya dalam menggunakan media sosial. Penelitian ini menggunakan metode kualitatif melalui analisis kepustakaan dengan telaah tematik hadis (maudhu’i), kritik sanad dan matan untuk memastikan otentisitas riwayat, serta analisis terhadap regulasi hukum siber di Indonesia, termasuk Undang-Undang Informasi dan Transaksi Elektronik (UU ITE). Hasil penelitian menunjukkan bahwa prinsip-prinsip moral seperti adab al-ḥiwār, pengendalian emosi, tazkiyah al-nafs, dan penguatan ukhuwah dapat diterjemahkan ke dalam strategi preventif yang aplikatif dalam pendidikan, keluarga, dan komunitas digital. Selain itu, integrasi nilai-nilai hadis dengan kerangka regulatif modern, seperti UU ITE, memungkinkan pendekatan yang lebih komprehensif dalam penanganan cyberbullying, termasuk pemanfaatan mekanisme edukatif dan rekonsiliatif yang sejalan dengan spirit islah. Penelitian ini menegaskan bahwa perundungan siber bukan hanya problem teknologi, tetapi persoalan etik dan spiritual yang memerlukan sinergi antara pembinaan karakter, literasi digital, dan kebijakan hukum. Temuan ini diharapkan memperkaya diskursus etika digital Islam dan memberi arah bagi pengembangan modul literasi digital berbasis hadis.